1998
DOI: 10.1016/s0370-2693(98)00084-7
|View full text |Cite
|
Sign up to set email alerts
|

Stationary black holes in a generalized three-dimensional theory of gravity

Abstract: We consider a generalized three-dimensional theory of gravity which is specified by two fields, the graviton and the dilaton, and one parameter. This theory contains, as particular cases, three-dimensional General Relativity and three-dimensional String Theory. Stationary black hole solutions are generated from the static ones using a simple coordinate transformation. The stationary black holes solutions thus obtained are locally equivalent to the corresponding static ones, but globally distinct. The mass and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In the string frame, a set of static and stationary solutions of Brans-Dicke theory, β = 4 and F = 0, was found in [10,11]. Here we consider similar solutions in the Einstein frame.…”
Section: Brans-dicke Theorymentioning
confidence: 95%
See 2 more Smart Citations
“…In the string frame, a set of static and stationary solutions of Brans-Dicke theory, β = 4 and F = 0, was found in [10,11]. Here we consider similar solutions in the Einstein frame.…”
Section: Brans-dicke Theorymentioning
confidence: 95%
“…For the Brans-Dicke case we had found a set of static and stationary solutions which are similar to [10,11] but are obtained in the Einstein frame. For the EMD case we found two new classes of spinning solutions: electric and magnetic.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Each different ω has a very rich and non-trivial structure of solutions with many black holes, which can be considered on its own. Here we do not attempt to comment on the whole set of solutions of the different theories 51,52 . For electric and magnetic rotating solutions see 56,57 .…”
mentioning
confidence: 99%
“…The interest in lower-dimensional theories of gravity has dramatically increased with the discovery [1,2] that three-dimensional general relativity with a negative cosmological constant admits a black hole solution (called BTZ), which, apart from being asymptotically anti-de Sitter, exhibits features closely related to the Schwarzschild and Kerr solutions. Further generalizations have shown that three-dimensional theories of gravity have a very rich structure of black hole solutions [3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%